IMPLEMENTATION OF DIGITAL LITERACY IN THE LEARNING PROCESS AT SD ISLAM KHALIFAH SERANG - meilany, fafa fauziah; Hakim, Zerri Rahman; Setiawan, Sigit (JPSD (Jurnal Pendidikan Sekolah Dasar), 2024)
The internet has made everything more accessible, including education, as schools and universities can now provide high-quality education. This research aims to describe the strategies teachers use to implement digital literacy in the learning process and to explain the implementation of digital literacy in the 4th grade at SD Islam Khalifah Serang. The research uses a qualitative method by exploring participants’ perspectives through observations, interviews, and data collection. The results show that teachers effectively incorporate digital literacy into the learning process. The school also supports teachers by providing adequate learning facilities. Besides improving students’ writing, sentence structuring, and reading abilities, implementing digital literacy in the learning process can also enhance their skills in using social media. In conclusion, implementing digital literacy at SD Islam Khalifah Serang includes developing lesson plans, conducting learning activities, strategizing the integration of digital literacy into the learning process, and preparing teachers before starting the lessons